Research on Language Teaching and Learning: Advances and Projection - Abad, José Vicente (Universidad Católica Luis Amigó, 2021)
In 2010, teachers from the B.A. in English Teaching at Universidad Católica Luis Amigó formed CILEX (Construcciones Investigativas en Lenguas Extranjeras). Research and teaching in the program have grown synergistically ever since, but ten years down the road it was time to take stock of our research to project the direction in which we wanted to move forward. This book is the result of that effort to recognize our shared history and thus propel our upcoming academic endeavors. The book starts out by presenting the epistemological foundations of CILEX, which is based on the threefold notion of the language teacher as an intellectual, an academic, and an educator. It thereon explains the system that arranges our academic production within five thematic nodes: cultural studies, language policy, literacies, language teacher education, and language assessment. Each chapter reports on one or two studies in which the authors participated as leading researchers or advisors. Hence, the book also reflects the formative research tradition that characterizes most of our practice. Having language teacher education as a binding thread that cuts across the entire volume, authors present their particular perspective on topics as varied as college academic performance, early childhood literacy, language policy appropriation, teacher educators' assessment literacy, student teachers' practicum identity crisis, research training in teacher education, and critical reading instruction. This book condenses the work of a group of teacher educators who believe in the power of research to galvanize teaching and inspire positive educational change. As readers go through its pages, it is our hope they will be able to recognize not only the singular value of each individual chapter but also the richness of our collaboration, which constitutes the fabric of our identity as an academic community.